Six contributions of information governance towards transparency and anti-corruption - García-Morales, Elisa (Anuario ThinkEPI, 2016)
An information governance program promoting strategic, coordinated, collaborative action on data and documents can contribute to the fight against corruption. Transparency and anti-corruption practices should be social imperatives for all organizations. This paper is a reflection based on the author´s experience as a consultant in the redesign of the procurement process for an oil and gas company. Data and documents are used as the main evidence for the actions taken.